Blue Moon Promise - Coble, Colleen (Nashville, Tenn. : Thomas Nelson, 2012)
Lucy Marsh has lost everything but her determination to provide for her brother and sister. When she realizes her father's death was no accident, she decides to accept a proxy marriage in order to get her siblings out of harm's way. But trouble follows her to Wichita Falls, Texas, and nothing there is as she expected.
Keywords: Ranchers -- Fiction -- Texas; Man-woman relationships -- Fiction; Brothers and sisters -- Fiction; Texas -- Fiction; Christian fiction; Love stories